Pengetahuan Masyarakat Kecamatan Ngemplak, Boyolali tentang Penggunaan Antibiotik tanpa Resep Dokter - Selma Utami Wailissa; Agnes Prawistya Sari; Hanugrah Ardya (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Antibiotics are essential drugs for treating bacterial infections. The inappropriate use of antibiotics is often due to a lack of knowledge, leading to increased antibiotic resistance. Currently, public awareness of antibiotic resistance is deficient. WHO found that in 12 countries, including Indonesia, 53-62% of people stop taking antibiotics when they feel better. Antibiotic resistance has become a global threat, prompting WHO to coordinate campaigns to raise public awareness. This study aims to assess public knowledge regarding antibiotics without a doctor's prescription in Ngemplak District, Boyolali, using a descriptive method with a questionnaire on 100 respondents. The results showed that public knowledge is still low: 8% good, 35% moderate, 57% poor, and the attitude towards using antibiotics without a prescription is mostly moderate (62%).